The diary [large type] - Goudge, Eileen (Thorndike Press large print core, 2009)
When two grown daughters discover their mother's diary in her attic, they are stunned to learn her true love was not their father. But is all as it seems? That's the mystery they must unravel as their mother lies near death in a nursing home. Only the pages of her diary can provide the clues. The Diary is a love story. It's also the story of a family and the question that all adult children ask themselves at some point: How well do you really know your parents?